Mental health difficulties, coping mechanisms and support systems among school-going adolescents in Ghana: a mixed-methods study - Addy, Noella Dufie; Agbozo, Faith; Runge-Ranzinger, Silvia; Grys, Pauline (PLOS ONE, 2021)
Background Although adolescents are highly vulnerable to mental health challenges, they receive little attention, especially in developing countries. We investigated the mental health difficulties (MHDs) faced by adolescent students in four senior high schools in Ghana, their coping strategies and support systems. Methods In this convergent mixed-methods study, quantitative data was obtained using validated strengths and difficulties questionnaire to assess the mental health of 405 adolescents. Qualitative data was collected through in-depth interview with 18 teachers and seven focused group discussions with 35 students. Adjusted odds ratios (OR) for MHDs were estimated through ordinal logistic regression in Stata 14.2. Qualitative data was analyzed inductively and deductively using ATLAS.ti 7.1. Results Over half (58.5%) experienced peer (20.5%), emotional (16.3%), conduct (13.3%) and hyperactivity (3.0%) problems, whereas 5.4% exhibited prosocial behaviours. MHDs were associated with females (OR = 2.27, 95% CI: 1.47-3.50), bullying (OR = 1.72, CI: 1.07-2.75), domestic violence (OR = 1.87, CI: 1.10-3.17), substance abuse (OR = 8.14, CI: 1.41-46.8), academic pressure (OR = 2.40, CI: 1.30-4.42) and self-perceived poor school performance (OR = 7.36 CI: 2.83-19.16). Qualitatively, we identified financial challenges, spiritual influences, intimate relationships, bullying, and domestic violence as the main themes attributed to MHDs. Coping strategies included isolation, substance use and spiritual help. The main school-based support system was the guidance and counselling unit, but there were complaints of it been ineffective due to trust and confidentially issues, and non-engagement of qualified counsellors. Conclusions As many triggers of MHDs emanate in schools, we need mental health-friendly school environments where trained psychotherapists head counselling centres. We propose incorporating mental health education into school curricula and generating surveillance data on adolescent’s mental health.